(untitled) (Journal of Parents and Teachers, 2026)
A study carried out at the University of Pennsylvania and published in the journal *Proceedings of the National Academy* has concluded that men’s brains deteriorate three times faster than women’s. This deterioration occurs primarily in the areas of the brain responsible for reasoning, calculation, planning and concept formation. In light of this finding, we present here ten research findings on the brain and learning, which may help to support healthy development and learning at different stages of life.